Application of wound cleansing using 0.9% NaCl to avoid damage to skin integrity in patients with diabetic ulcers in the space swallow - Andi Suriani; Syaharuddin Syaharuddin; Tri Damayanty Samsul; Fardi Fardi (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Diabetic ulcers are defined as erosion of the skin that extends from the dermis layer to deeper tissue, resulting from various factors, namely neuropathy, ischemia and infection, resulting in damage to the patient's skin integrity. Bhayangkara Hospital Makassar Medical Records 2022 number of diabetic ulcer patients was 5,743 people, the number of inpatient diabetic ulcer patients was 586 people (2.70%), and the number of outpatients was 5,157 people (4.38%). This research aims to find out a general description of the application of wound cleaning using 0.9% NaCl to avoid damage to skin integrity in patients in the PMerak Room, Bhayangkara Hospital, Makassar. This research method uses descriptive research with a case study approach, using 4 effective methods for collecting data, namely Interview, Observation, Physical Examination and documentation methods. The results of applying wound cleaning with 0.9% NaCl to patients who had diabetic ulcers in the swallow room at Bhayangkara Makassar Hospital for 3 days showed that the nursing problem was that damage to skin integrity had not been resolved. After implementing the intervention, the result was that pus in the wound was reduced, and a new network emerged. Conclusion: After applying wound care using 0.9% NaCl liquid, "Skin integrity has not been resolved in diabetic ulcer wounds. On the last day of the study, the surgical wound on the little finger had dried, and the base of the second, third and fourth toes of the right toe looked scaly and dry and sore. In the ulcers, new tissue appears in the center of the wound.